2014
DOI: 10.1042/cs20130081
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus is a potent inhibitor of activated hepatic stellate cell functions in vitro and in vivo, while demonstrating anti-angiogenic activities

Abstract: Progression of liver fibrosis to HCC (hepatocellular carcinoma) is a very complex process which involves several pathological phenomena, including hepatic stellate cell activation, inflammation, fibrosis and angiogenesis. Therefore inhibiting multiple pathological processes using a single drug can be an effective choice to curb the progression of HCC. In the present study, we used the mTOR inhibitor everolimus to observe its effect on the in vitro activation of hepatic stellate cells and angiogenesis. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…HSC activation and ECM genesis. A variety of studies have revealed that mTOR inhibitors can decrease the degree of liver fibrosis via mTOR signaling pathway [35,36]. HIF-1, serving as a mediator of adaptation to hypoxia and pathological response, is a physiological regulator of gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…HSC activation and ECM genesis. A variety of studies have revealed that mTOR inhibitors can decrease the degree of liver fibrosis via mTOR signaling pathway [35,36]. HIF-1, serving as a mediator of adaptation to hypoxia and pathological response, is a physiological regulator of gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PIGF induced proliferation and migration of cultured HSCs via activation of ERK1/2. Another study indicating the role of angiogenesis in the regulation of the fibrogenic process investigated the effects of everolimus, which inhibits collagen production by activated HSCs, as well as their contraction and transition toward an activated status [42]. The mechanism of angiogenesis is also tightly regulated through angiogenesis inhibitors.…”
Section: Angiogenic Cytokinesmentioning
confidence: 98%
“…Other mTOR inhibitors, sirolimus and everolimus, also reduced fibrosis progression and portal hypertension in BDL rats (Patsenker et al 2011). Moreover, everolimus worked via multiple mechanisms, including inhibiting angiogenesis and preventing the tube formation and migration of liver sinusoidal endothelial cells (Piguet et al 2014). The clinical study using everolimus monotherapy in liver transplantation recipients showed the less serum expression of TGF-β1, but no differences in inflammatory activity, in APRI test, or in liver elastography (Fernandez-Yunquera et al 2014).…”
Section: Down-regulating Myofibroblast Activation and Ecm Productionmentioning
confidence: 97%